Tolerance of noncompliance: Discretion rather than simple rules? - Forteza, Álvaro; Noboa, Cecilia (Estudios de Economía, 2019)
We argue that societies sometimes choose not to enforce the law to gain “flexibility”. Especially developing countries face a dilemma between discretion and commitment to only partially-contingent rules. Rules are good for incentives, but discretion may be more “flexible”. We embed this dilemma in a political model and show that citizens will not support strong enforcement institutions unless the state is able to commit to sufficiently sophisticated redistributive policies.